Pladias platform: Technical description of the database structure - Novotný, Petr; Brůna, Josef; Chytrý, Milan; Kalčík, Vojtěch; Kaplan, Zdeněk; Kebert, Tomáš; Rohn, Martin; Řezníčková, Marcela; Štech, Milan; Wild, Jan (Biodiversity data journal, 2022)
BACKGROUND: Digitising and aggregating local floristic data is a critical step in the study of biodiversity. The integrative web-based platform Pladias, designed to cover a wide range of data on vascular plants, was recently developed in the Czech Republic. The combination of occurrence data with species characteristics opens many opportunities for data analysis and synthesis. NEW INFORMATION: This article describes the relational structure of the Pladias database service (PladiasDB) and the context of the platform architecture. The structure is relatively complex, as our goal was to cover: (i) species occurrence records, including their management, validation and export of revised species distribution maps, (ii) data on species characteristics with quality control tools using defined data types and (iii) separate user interfaces (UI) for professionals and the general public. We discuss the approaches chosen to model individual elements in PladiasDB and summarise the experience gained during the first five years of operation of the Pladias platform.
Keywords: database; vegetation; flora; relational database model; tree hierarchy; trait; occurrence; Czech Republic; plant; species; botany